Influence of electrode cooling on recast layers and micro crack in EDM of titanium - Abdulkareem, Suleiman; Khan, Ahsan Ali; Mohamed , Konneh (Trans Tech Publications, Switzerland, 2011)
Electrical discharge machining (EDM) process is a manufacturing method for shaping hard metals and formation of deep and complex shaped hole by spark erosion in electrical conductive materials such as metals, metallic alloys, ceramics etc. EDM process is achieved by a series of recurring electrical discharges between the electrode and workpiece in the presence of dielectric fluid. EDM unique feature of using thermal energy to machine conductive materials irrespective of material hardness has been its major advantage in the manufacture of aerospace, surgical, mould, die, automotive and as well as sport components. The effectiveness of EDM process depends among other factors on the thermal properties of the electrode material. The objective of this study is to study the influence of electrode cooling on recast layers and micro crack in EDM of titanium. The machining parameters investigated in the present study are current intensity (I), pulse on-time (Ton), pulse off-time (Toff) and gap voltage (V), which are of great interest for EDM researchers. The copper electrode is used to EDM titanium workpiece at room temperature and at sub-zero temperature using liquid nitrogen. The influence of cooling of copper electrode on recast layers and micro crack on titanium were investigated using scanning electron microscope (SEM) and has been reported in this study.